Wildfire behaviour data for an experimental crown fire in thinned boreal black spruce, Alberta, Canada, 2019-05-11 - Thompson, Dan K (Zenodo, 2020)
Data describing an experimental forest fire in Wabasca, Alberta, Canadain May 2019.